Potential Analysis of Low Economic Value Fish in Lamongan Regency, East Java, Indonesia - Anam Choirul; Harini Noor; Damat Damat; Wahyudi Ahmad; Witono Yuli; Kuswardhani Nita; Azus Shony Azar Moh; Anne Olga; Rachmawati Diana (E3S Web of Conferences, 2021)
The purpose of this study was to determine the potential of low commercial value fish species in Lamongan Regency, East Java, Indonesia. The processed data included primary and secondary data. Data were processed using the LQ method and analyzed descriptively by way of compiling data into tables. The survey results showed that there are ten types of low commercial value fish in Lamongan Regency, East Java, Indonesia, namely Sardinella fimbriata (Tembang fish), Leiognathus bindus (Peperek fish), Harpadon nehereus (Puso fish), Sardinella lemuru, (Lemuru fish), Saurida tumbil (Beloso fish), Gerres abbreviatus (Kapasan fish), Anodontostoma chacunda (Juwi fish), and Cynoglossus lingua (Lidah fish). The results of the LQ method showe that there are three types of fish that have the potential to be made of high economic value products, namely L. bindus (11.36), A. chacunda (2.35), and S. fimbriata (2.32). Fish Auction (TPI) that has the potential in terms of fish productivity to be developed is TPI Weru, Lamongan, East Java, Indonesia. The typology of fishermen in TPI Weru has less experience working as a fisherman than other TPI but the level of education is higher and the age of fishermen is younger so that it affects the productivity of fish catches.